2019
DOI: 10.1002/ece3.5410
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife surveillance using deep learning methods

Abstract: Wildlife conservation and the management of human–wildlife conflicts require cost‐effective methods of monitoring wild animal behavior. Still and video camera surveillance can generate enormous quantities of data, which is laborious and expensive to screen for the species of interest. In the present study, we describe a state‐of‐the‐art, deep learning approach for automatically identifying and isolating species‐specific activity from still images and video data. We used a dataset consisting of 8,368 images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Technologies that allows cameras to determine what entity lies within their field-of-view, has allowed for detection of human faces, objects and animals. In [ 25 ] it was shown that the use of machine learning techniques, a CCTV camera were capable of differentiating between different kinds of wildlife using Convolutional Neural Networks (CNN). Another example of entity awareness in CCTV systems were demonstrated in [ 26 ], where they demonstrated a way for cameras to search for faces, using cameras on a public transport system.…”
Section: Devicesmentioning
confidence: 99%
“…Technologies that allows cameras to determine what entity lies within their field-of-view, has allowed for detection of human faces, objects and animals. In [ 25 ] it was shown that the use of machine learning techniques, a CCTV camera were capable of differentiating between different kinds of wildlife using Convolutional Neural Networks (CNN). Another example of entity awareness in CCTV systems were demonstrated in [ 26 ], where they demonstrated a way for cameras to search for faces, using cameras on a public transport system.…”
Section: Devicesmentioning
confidence: 99%
“…Technologies that allows cameras to determine what entity lies within their field-of-view, has allowed for detection of human faces, objects and animals. In [17] it was shown that the use of machine learning techniques, a CCTV camera were capable of differentiating between different kinds of wildlife using Convolutional…”
Section: Elements Of a Citymentioning
confidence: 99%
“…Similarly, the role of IoT, robotics, and computer vision techniques in various animal and pest monitoring applications has been extensively researched [ 18 , 19 , 20 , 21 ]. In Reference [ 22 ], Ruilong Chen et al developed an automated image classification algorithm to identify the wild animal badgers from domestic animals in farm buildings. Two deep learning-based image classification frameworks were used in this experiment.…”
Section: Introductionmentioning
confidence: 99%